1970
DOI: 10.1021/ma60013a024
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ferrocenylmethyl Acrylate and Ferrocenylmethyl Methacrylate Polymerization. Preparation of Polymeric Ferricinium Salts

Abstract: Communications to the Editor 105 Figure 4. Generalized retention curve for polypropylene using hexadecane probe (column C) O, melting curve, first series; , melting curve, second series.those obtained by other procedures is a further corroboration, as is the fact that the values of Tm are not decreased from the expected values for the polymers used. If there were any appreciable solution of the probe molecules in the crystalline regions, some depression of 7", would be anticipated.If further experiments verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

1971
1971
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…70% yield and very high purity. The applied procedure proved to be superior to the published recipes, [14][15][16][17] which take advantage of methacrylic chloride as the esterification reagent. In the latter case, side products are formed that are hard to remove to the extent needed for anionic polymerization.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…70% yield and very high purity. The applied procedure proved to be superior to the published recipes, [14][15][16][17] which take advantage of methacrylic chloride as the esterification reagent. In the latter case, side products are formed that are hard to remove to the extent needed for anionic polymerization.…”
Section: Resultsmentioning
confidence: 95%
“…[14][15][16][17] Reduction of ferrocenyl carbaldehyde 1 was achieved using NaBH 4 in methanol solution, to afford hydroxymethylferrocene 2 in essentially quantitative yields. Subsequently, a mixture of 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…* Polymerization studies on vinylferrocene have been reported by various investigators,**4 including a comprehensive study by Baldwin and Johmon. 6 The polymerization studies on other alkenylferrocenes have been very limited;* however, studies have now been extended to include isopropenylferrocene. This paper describes the attempted homopolymerization of isopropenylferrocene and its copolymerization with methyl methacrylate and styrene by freeradical initiation.…”
Section: Polymerization Studies Of Isopropenylferrocenementioning
confidence: 99%